Synthesis and structure-activity relationships of small-molecular di-basic esters, amides and carbamates as flaviviral protease inhibitors - Sundermann, Tom R.; Dražić, Tonko; Klein, Christian D. (European journal of medicinal chemistry, 2019)
Inhibitors of the flaviviral serine proteases, which are crucial for the replication of dengue and West-Nile virus, have attracted much attention over the last years. A dibasic 4-guanidinobenzoate was previously reported as inhibitor of the dengue protease with potency in the low-micromolar range. In the present study, this lead structure was modified with the intent to explore structure-activity relationships and obtain compounds with increased drug-likeness. Substitutions of the guanidine moieties, the aromatic rings, and the ester with other functionalities were evaluated. All changes were accompanied by a loss of inhibition, indicating that the 4-guanidinobenzoate scaffold is an essential element of this compound class. Further experiments indicate that the target recognition of the compounds involves the reversible formation of a covalent adduct.
Gesehen am 16.07.2019